Implementation Of Problem Based Learning To Increase Student's Motivation And Learning Outcomes By Using Video Media In Creative Products And Entrepreneurship Lessons In Class XI TKJ SMK Private Indonesia Building - Riris Melati Sinaga (UMSU, 2021)
This research was carried out at the Indonesian Private Vocational High School Building in Class XI Computer Network Engineering where the learning outcomes of students for the material for Business Opportunities for Goods and Services Products online in the subjects of Creative Products and Entrepreneurship were low. This study aims to increase student motivation and learning outcomes in the subjects of Creative Products and Entrepreneurship Class XI TKJ during the Covid 19 pandemic with a distance learning model (Online learning). The results of observations made turned out to be in the process of distance learning and face-to-face encounters with many obstacles and problems, especially for students, it is not easy in this distance learning to provide an understanding of the material presented / given to students through the google classroom application platform and very low meet rooms. resulting in very low student learning outcomes. The research method used in this distance learning uses the google classroom application platform with the research subjects of class XI TKJ students. Data collection techniques using evaluation in the form of knowledge assessment (google form) and LKPD. The data analysis method is descriptive. The results obtained from this study the application of problem based learning using video media can increase students' motivation and learning outcomes in the subjects of creative products and entrepreneurship. This is evident from the results obtained at first that only 38.46% of students mastered the material, in the first cycle it reached 65.38% of students who completed and in the second cycle it reached 80.76% of students who completed. The conclusion obtained from this study is that the application of problem based learning using video can increase students' motivation and learning outcomes in the subjects of creative products and entrepreneurship